PROFESSIONAL DEVELOPMENT NEEDS OF STAKEHOLDERS IN EDUCATION: A COMPARATIVE STUDY OF BASIC SCHOOLS IN THE CENTRAL REGION OF GHANA - Dampson, Dandy George; Mensah, Dominic Kwaku Danso (PEOPLE: International Journal of Social Sciences, 2018)
The main purpose of the study was to find out the professional development needs of teachers, head teachers and Circuit Supervisors (CS) in the Basic Schools in the Central Region of Ghana. The study employed the descriptive survey design. The simple random sampling technique was used to sample 209 teachers whilst the purposive sampling technique was also used to sample 29 head teachers and 11 CS for the study. A self-designed questionnaire with reliability co-efficient of 0.87 was used to collect data from the respondents. Data collected from the respondents was analysed into frequency counts and percentages. The study established that the teachers, head teachers, and CS across both geographical locations of the study participate in staff development programmes. Nevertheless, the respondents in urban schools experience more participation than their colleagues in rural-urban schools. It was further revealed that the professional development needs of teachers, head teachers and Circuit Supervisors (CS) varies across the two sites of the study. The study, therefore, recommended that the types of professional development programmes should be tailored to meet the needs of stakeholders in education (i.e. teachers, head teachers, and circuit supervisors).